SoTL in verse - Gilpin, Lorraine S. (Teaching and Learning Inquiry, 2013)
This piece offers an overview of the Scholarship of Teaching and Learning (SoTL) in a nontraditional genre. It glances backward to the catalyst for the movement and traverses the context of SoTL today. Grounded in foundational literature of the field, it explores ideas about SoTL, including its purpose, nature, and characteristics. It underscores the importance of the symbiotic relationship between teaching and research and highlights improved student learning as the primary focus of SoTL inquiries. Embedded within the piece is the need for SoTL engagement to transform the educational landscape in morally and socially responsible ways. SoTL is laden with an ethic of reflexivity evidenced in actions that improve learning and the contexts in which teaching and learning occur for those in the core of the inquiry as well as others by extension.